2004 IEEE International Conference on Communications (IEEE Cat. No.04CH37577) 2004
DOI: 10.1109/icc.2004.1312902
|View full text |Cite
|
Sign up to set email alerts
|

An envelope process for multifractal traffic modeling

Abstract: In this paper, a novel envelope process for multifractal traffic modeling is introduced. The envelope process is an upper bound for the amount of work arrived in a multifractal Brownian motion process. The time scale of interest of a queueing system fed by a multifractal stream is computed. Simulation experiments using both real and synthetic data show that the proposed model is accurate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 12 publications
(15 reference statements)
0
25
0
4
Order By: Relevance
“…In other words, some IP flows can be modelled by monofractal processes, while others call for more complex multifractal modelling. There is no definite model that should be used for all network scenarios [4][5][6][7]. The best model can only be identified by measuring the characteristics of a specific flow.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, some IP flows can be modelled by monofractal processes, while others call for more complex multifractal modelling. There is no definite model that should be used for all network scenarios [4][5][6][7]. The best model can only be identified by measuring the characteristics of a specific flow.…”
Section: Introductionmentioning
confidence: 99%
“…Such overestimation is due to the use of a single parameter, the Hurst parameter, to describe burstiness of the traffic. This parameter, which is a constant value, is a global measure of explosiveness and is unable to capture the activity on small time scales of multifractal traffic [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Referring to [15], candidates of optimized condition are given by either (a) (5) where (6) under which we have (7) or (b) one of the following conditions (8) where , and denotes the greatest integer less than or equal to , and we have (9) The meaning of conditions (5) and (8) is as follows. Condition (5) implies sending all I frames and through frames with probability one, sending with probability , and dropping through .…”
Section: (4)mentioning
confidence: 99%
“…Consider the sequence , of which the mean is given by and its variance is given by (21) Given and , we now construct an objective function of as transmission rate of the queueing system, as follows: (22) where Finally, the effective bandwidth is obtained as (23) 4) Multifractal Scaling: Recent measurement and simulation studies have revealed that wide area network traffic and VBR video traffic display complex statistical characteristics-possibly multifractal scaling-on fine timescales, in addition to the well-known property of self-similar scaling on coarser timescales in the context of LRD [10]. In [9], it is shown that unreasonable overestimation of the equivalent bandwidth of a flow can be made if scaling at small scales are not considered in the modeling process, e.g., fractional Brownian motion. If the multitime scaling property is essential, the video traffic can be modeled as a combination of fractional Brownian motion and multifractal cascade to account for the small-scale effect corresponding to subframe scale using the method described in [10] …”
Section: ) Fractional Brownian Motion (Fbm)mentioning
confidence: 99%
See 1 more Smart Citation